Enhancing tumoricidal effects of radiation therapy with low-intensity focused ultrasound in murine breast cancers - Schumacher, Michelle Marie; Gutierrez Chavez, Claudia; Malachowska, Beata; Pandey, Sanjay; Tchaikovskaya, Tatyana; Singh, Saurabh; Barry, Steve; Macedo, Rodney; Guha, Chandan (Frontiers in Acoustics, 2025)
IntroductionFocal cancer therapies fail to cure metastatic disease. Our prior studies indicated that Low Intensity Focused Ultrasound (LOFU) boosts antitumoral immunity in murine melanoma and prostate cancer. We hypothesized that LOFU, combined with radiation therapy (RT), could stimulate an immunogenic tumor microenvironment (TME) in murine breast cancers, potentially acting as an in-situ vaccine.MethodsWe evaluated LOFU ± RT in TSA and E0771 breast cancer models in BALB/c and C57BL/6 mice, respectively, and measured intra-tumoral temperatures and gene expression to assess acoustic thermal stress using quantitative RT-PCR.ResultsFlow cytometry and gene expression showed that LOFU induced unfolded protein response pathway and heat shock protein RNA. LOFU modified the immune contexture in the TME of both tumor models, notably by increasing CD8+ T cell infiltration, including anti-gp70 CD8+ T cells, and reducing the RT-induced regulatory T cell response in TSA tumors.DiscussionLOFU, as a non-ablative therapeutic, primes the TME and augments control of murine breast cancers by inducing tumor-specific adaptive immune responses.